Pengaruh Fraksi Daun Asam Jawa (Tamarindus indica L.) terhadap Fungsi Hati dan Ginjal Tikus Diinduksi Parasetamol - Rahimah, Sitti; Awaluddin, Akbar; Wahyuddin, Nurzadrina (Jurnal Kefarmasian Indonesia, 2022)
Liver and kidneys play a role in the metabolism and excretion of substances that enter the body, they become targets for toxicity from xenobiotics and other chemicals including drugs. Exogenous antioxidants are needed to overcome and prevent oxidative stress. Fraction of tamarind leaf extract (Tamarindus indica L) has antioxidant activity, it has the potential to protect the body from free radicals. This study aimed to determine the effect of giving tamarind leaf fractions on AST, ALT and creatinine levels in rats (Rattus norvegicus) induced with paracetamol. Experimental animals were divided into 4 groups. Group I was given paracetamol induction (negative control), group II was given the ethyl acetate fraction and induced paracetamol, group III was given the n-hexane fraction and induced paracetamol, and group IV was without treatment (positive control). Statistical analysis using One Way Anova test and LSD (Post Hoc) showed that the ethyl acetate fraction was not significantly different (p-value >0.05) with the positive control group and the n-hexane fraction group, but significantly different from the negative control group (p -value